RAGAM TINDAK TUTUR PERMINTAAN MAAF MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA INGGRIS FKIP-UIKA BOGOR - Retnowati, Nanik (JURNAL TARBAWIYAH, 2015)
Knowing the rules which organize the target language has been the concern of many experts to facilitate language learning and teaching. The rules are not only in the level of sentence but also in the level of discourse. This study is trying to find out the rules in discourse level, especially the pattern of speech act on asking for apology. This study is aimed at knowing the speech act set of apologizingy made by students to lecturers, students to students, the acceptability of the patterns, and the factors which may influence the acceptability of the expressions used for apology. There were thirty five respondents; twenty respondents should give information about expressions for apology, fifteen other respondents give their opinion about the acceptability of the expressions.Using the procedure in discourse analysis, the writer found that respondents produced different set of speech act. Other speech act may accompany speech act for apology both before and after it; i.e.  greeting, explanation, acknowledgement of responsibility, an offer of repair, request, thank, and informing. The study also found the most common pattern;i.e.apology+ aknowledgment for student-lecturer interaction and apology+explanation for student-student interaction.The acceptability of the pattern does not only depend on the linguistic choice such as lexical, grammatical, and prosodic features  but also paralinguistic features such as gestures, eye contact, body movement. Another important aspect for acceptability is the interpersonal relationship between the participants and their background. The findings in this study would give illustration about the rules of apology used by the learners. If it is compared to rules in  the target language(English), using contrastive analysis procedure, we would find the obstacles meet by the students in acquiring the speech act of English apology.